Increasing Interest and Knowledge about Verticulture Cultivation among Adolescents at the Gelora Indah Mosque Orphanage, North Purwokerto: Peningkatan Minat dan Pengetahuan tentang Budidaya Vertikultur pada Remaja Panti Asuhan Masjid Gelora Indah Purwokerto Utara - Agus Suroto; Tarjoko; Eka Oktaviani (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Orphanages play an important role in replacing the role of parents in nurturing, looking after, and providing guidance to children so that they become adults who are valuable and responsible for themselves and society in the future. The goal of the community service was to increase the interest and knowledge of teenagers at the Gelora Indah Mosque Orphanage, North Purwokerto, regarding vertical-culture (verti-culture) cultivation techniques. Verticulture technique was chosen because of the potential for narrow yard land, which can be used as land for agricultural crop production, especially plants that are suitable for vertical cultivation. This activity can be used as a provision for achieving food self-sufficiency at the household level and as a basis for producing agricultural products that can be used as input for entrepreneurship from an early age. The community service was conducted from March to May 2023 with all the teenagers of Gelora Indah Mosque Orphanage. The methods were a pre-test, a transfer of knowledge about verti-culture cultivation techniques, cultivation practices, harvesting, and finally, post-tests for the last evaluation. This activity can increase participants' interest and knowledge about the concept of verti-culture by 83.34%, about the needs for verti-culture installation by 66.67%, and about the benefits of verti-culture by 100%. Activities in the form of transfer of knowledge about post-harvest handling and processing, as well as marketing techniques for processed and fresh agricultural products, are needed to support the long-term benefits of this activity.